Communicating ocean and human health connections: An agenda for research and practice - Reamer, Marcus B. (Frontiers in Public Health, 2022)
The emergence of ocean and human health (OHH) science as a distinct scholarly discipline has led to increased research outputs from experts in both the natural and social sciences. Formal research on communication strategies, messaging, and campaigns related to OHH science remains limited despite its importance as part of the social processes that can make knowledge actionable. When utilized to communicate visible, local issues for targeting audiences, OHH themes hold the potential to motivate action in pursuit of solutions to environmental challenges, supplementing efforts to address large-scale, abstract, or politicized issues such as ocean acidification or climate change. Probing peer-reviewed literature from relevant areas of study, this review article outlines and reveals associations between society and the quality of coastal and marine ecosystems, as well as key themes, concepts, and findings in OHH science and environmental communication. Recommendations for future work concerning effective ocean and human health science communication are provided, creating a platform for innovative scholarship, evidence-based practice, and novel collaboration across disciplines.